The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3109/14647273.2014.921337
|View full text |Cite
|
Sign up to set email alerts
|

Duration of luteal support after IVF is important, so why is there no consistency in practice? The results of a dynamic survey of practice in the United Kingdom

Abstract: Luteal support is considered as an essential component of IVF treatment following ovarian stimulation and embryo transfer. Several studies have consistently demonstrated a benefit of luteal support compared with no treatment and whilst a number of preparations are available, no product has been demonstrated as superior. There is an emerging body of evidence which suggests that extension of luteal support beyond biochemical pregnancy does not confer a benefit in terms of successful pregnancy outcome. We perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…In the 2018 survey 72% of respondents administered LPS until 8-10 gestational weeks, and the most recent 2019 survey revealed that 65% of the respondents continued LPS until 10-12 gestational weeks. Another survey conducted in the United Kingdom's ART community yielded similar results (33). These ndings represent the perception that the quality of data regarding early cessation of LPS is weak and insu cient to recommend a change in practice.…”
Section: Durationsupporting
confidence: 57%
“…In the 2018 survey 72% of respondents administered LPS until 8-10 gestational weeks, and the most recent 2019 survey revealed that 65% of the respondents continued LPS until 10-12 gestational weeks. Another survey conducted in the United Kingdom's ART community yielded similar results (33). These ndings represent the perception that the quality of data regarding early cessation of LPS is weak and insu cient to recommend a change in practice.…”
Section: Durationsupporting
confidence: 57%
“…The general attitude among most practitioners has been that it is better to continue progesterone than to take a risk of a pregnancy loss using the earlier stop [ 19 21 ]. However, assisted reproductive technology (ART) treatment for infertility couple is not an easy task.…”
Section: Discussionmentioning
confidence: 99%
“…But, some doctors discontinued progesterone supplementation at 7 weeks of pregnancy and the other doctors continued it until the 12 weeks [ 19 22 ]. It was thought to be better to continue progesterone than to take a risk of miscarriage using the earlier stop [ 19 21 ]. However, the effect of early stop of progesterone supplementation or continuation for patients with poor ovarian response (POR) has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, local IVF protocols were followed at each participating clinic; however, this was not expected to influence patients’ assessment of ease of use and dosing convenience with the progesterone tablets. Finally, as the recommended duration for progesterone supplementation for LPS varies widely between IVF clinics (ranges from 2 to 12 weeks after oocyte retrieval), 47 patient experience with vaginal progesterone tablets for LPS beyond 14 days was not evaluated in the current audit.…”
Section: Discussionmentioning
confidence: 99%